Teacher’s Method in Stimulating Psychosocial Development in Early Childhood - Ekaningtyas, Ni Luh Drajati (Jurnal Pendidikan Anak Usia Dini Undiksha, 2020)
Psychosocial development is a psychological and social adjustment process in line with individual’s development from infancy to adulthood, based on eight stages of human psychological and social maturity. Therefore, the psychosocial development of early childhood and the method applied to stimulate it becomes important to be investigated.  This research aims to determine the methods applied by the teacher of early childhood education programs to stimulate early childhood psychosocial development, with the formulation of the research problem as follows: (1)  the teacher’s understanding of early childhood psychosocial development stimulation; (2) the method used by the teacher to stimulate psychosocial development of early childhood; (3) the results of the method that applied to stimulate psychosocial development of early childhood. This research uses descriptive qualitative method with the early childhood teachers as the key informant and early childhood parents as the additional informant. Data collection is done by observation, interviews, and documentation to answer the research problem. The results of this research are as follows: (1) the teacher’s understanding of psychosocial development stimulation is still more inclined to the social aspects; (2) the stimulation method applied has targeted all aspects of early childhood psychosocial development; (3) the results of the stimulation method applied shown in the positive progress of both psychological and social aspects of the psychosocial development. Keywords: psychosocial development, developmental stimulation, early childhood